Prevalence of ideal cardiovascular health metrics in children & adolescents: A systematic review. (December 2016) - Pacor, Justin M.; Younus, Adnan; Malik, Rehan; Osondu, Chukwuemeka U.; Aziz, Muhammad; Ogunmoroti, Oluseye; Younus, Muhammad Amir; Aneni, Ehimen C.; Spatz, Erica S.; Humayun, Choudhry; Virani, Salim; Blaha, Michael; et al.
Abstract: Background: Although the prevalence of ideal cardiovascular health (CVH) has been extensively studied, its distribution in younger populations is not well established. In this systematic review we aggregated available evidence to examine prevalence of ideal CVH metrics in the adolescent and children population. Methods: A MEDLINE database search was conducted for studies published between January 2010 and July 2015. To be included in the study, studies had to report prevalence data on at least four of the seven metrics. Each study was meticulously reviewed by two independent reviewers, and studies with prevalence percentages across different percentiles were included. Results: Overall 6 studies met the inclusion and exclusion criteria. BMI and diet were the only metrics for which all 6 studies reported prevalence of ideal. Prevalence of ideal for fasting plasma glucose was reported least frequently, with 2 of the studies failing to assess it. A prevalence of > 50% for ideal blood pressure or BMI was seen uniformly across all studies included in the review. By contrast, the healthy diet has the lowest prevalence among ideal CVH metrics ranging from 0 to 10%. Physical activity was the most variable with a range of 6.2–85.4%. Conclusion: Ideal diet and physical activity had the lowest prevalence among CVH metrics. Focused efforts on standardizing assessment of these metrics as well delineating strategies to achieve ideal CVH among children and adolescents are required. Highlights: Ideal diet and physical activity have an alarmingly low prevalence among CVH metrics in this age group Criteria for ideal CVH in children are variable and associated with differences in prevalence of ideal for certain metrics Our review highlights importance of modifying criteria for a younger population, specifically for diet and physical activity There is an opportunity for future studies to determine the appropriate age to begin monitoring all seven metrics Providers should work to shift the emphasis towards primordial prevention due to benefits on adult CVH and outcomes